18. REFLUX OF DUODENAL CONTENTS INDUCES ESOPHAGEAL CARCINOGENESIS (SCC, ADC). (24th September 2022) - Hashimoto, Naoki
Abstract: The incidence of esophageal cancer patients who have undergone distal gastrectomy is increasing recently. Distal gastrectomy is a good model for studying the clinical effects of duodenal content reflux. It is known that reflux of duodenal contents can induce mucosal injury, stimulate cell proliferation, and promote tumorigenesis. We examined the expression of COX2 and P53 in rat esophageal lesions induced by duodenal contents reflux after total gasytrectomy. Thirty 8 week old male wistar rats were exposed to duodenal content esophageal reflux. All animal underwent an esophagoduodenal anastomosis(EDA) with total gastrectomy in order to produce chronic esophagitis. Ten rats were the sham (Control). They were sacrified at the 40th week. Their esophagi were examined for HE, COX2, P53 and Proliferating cell nuclear antigen (PCNA). After 40 weeks of reflux, dysplasia(100%), squamous cell carcinoma(SCC)(40%) and adenocarcinoma (ADC) (30%)were found. PCNA Labeling index was higher in dysplastic and cancer tissue than that of normal. Overexpression of COX2 were shown in ADC and SCC. Wild type p53 accumulation were found in ADC, not in SCC. Moreover, SCC developed in places distant from the anastomosis compared to ADC. As compared with ADC, SCC is less frequently inflammatory. This means that histological features may depend on the volume of reflux contents; small amounts of reflux causes SCC and a large volume of reflux causes ADC. Reflux of duodenal contents into the esophagus led to ADC and SCC in rat. Small amounts of reflux causes SCC and a large volume of reflux causes ADC. COX2 may play an important role in esophageal cancer by duodenal content reflux. Our present results suggest an association between wild type P53 accumulation and COX2 expression in ADC, with no such relation seen in SCC.